The Candida quercitrusa strain Cq-C08 induces plant resistance to root-knot nematodes - Lu, Cuihua; Li, Erfeng; Liu, Rui; Chang, Nv; Lai, Yuqing; Wu, Yue; Wu, Weilong; Chen, Zhukan; Ling, Jian; Zhao, Jianlong; Mao, Zhenchuan (Frontiers in Microbiology, 2025)
IntroductionRoot-knot nematodes (RKNs), belonging to the genus Meloidogyne, are plant parasitic nematodes with a broad host range, causing substantial economic losses annually. The selection and utilization of novel biological control resources are crucial for managing RKNs diseases.MethodsThis study isolated Candida quercitrusa Cq-C08 from rhizosphere soil, which the efficacy of Cq-C08 against Meloidogyne incognita was investigated through laboratory experiments, pot and plot trials, and analysis of the transcriptomic data from cucumber roots treated with Cq-C08.Results and discussionThis study isolated Candida quercitrusa Cq-C08 from rhizosphere soil, and a series of experiments confirmed that the fermentation broth had a lethal rate of 100% against M. incognita J2s within 12 h and exhibited a significant repellent effect on the nematodes. In pot and plot tests, the strain Cq-C08 achieved a control effect over 50% against M. incognita and significantly promoted cucumber (Cucumis sativus, Zhongnong No. 6, China) growth. Inoculation experiments confirmed that the Cq-C08 strain could activate key immune signaling pathways of salicylic acid (SA) and jasmonic acid (JA). Split-root tests showed significant induced resistance of cucumber to M. incognita by 32.3%. Comparative transcriptome analysis confirmed that strain Cq-C08 could regulate the host’s basal immune response and oxidative burst response through SA, JA, and ethylene (ET) signaling pathways, and alter secondary metabolism, activating the synthesis of cucurbitacin and auxins, which promotes plant immune regulation and growth. These results prove that C. quercitrusa Cq-C08 has high control effects against M. incognita and the potential to be developed into a biological control product against root-knot nematodes.